Desvendando a importância do ecossistema manguezal através de uma ueps sob o enfoque ctsa - Silva, Carlos José Araújo da (2019)
The mangrove ecosystem has great economic, ecological and social relevance for the Guamaré (RN, Brazil) population. However, it has been threatened by human action. Hence, we sought to elaborate and implement a teaching method capable of corroborating with the process of training social-environmentally active and aware citizens, conducting debates on the importance of the mangrove ecosystem, the process of degradation and actions to be developed with the purpose to mitigate environmental damage on mangrove ecosystem. By knowing the school importance on raising awareness, it was possible to analyze the historical context of science education, and the successful practices throughout regarding the subject. Accordingly, the objective was to elaborate and evaluate the didactic relevance of the application of the Potentially Meaningful Teaching Units (PMTUS) under the Science, Technology, Society and Environment (STSE) approach by teaching about the mangrove ecosystem on a 7th grade elementary school class at the city of Guamaré, RN, Brazil. Regarding the methodological design, this is a qualitative research mixed with pedagogical intervention bias. Hence, firstly the school was visited and then a pre exam was applied to verify the students' previous knowledge. This information was essential for identification of appropriate and partially adequate subsumers so that they could later anchor new scientific knowledge addressed in the workshops. Based on this information, a PMTUS was developed under the STSE approach. Thus, the PMTUS was applied and then finally, a final evaluation. It was noted that the didactic intervention presented significant results, because when analyzing the data it was possible to notice that there was an advance ideas contextualization to combat the environmental mangrove issues caused by anthropic action such as improper waste disposal, shrimp farms construction, among others, highlighting the relevance of the STSE approach in science classes when presenting issues pertaining to Environmental Education. Finally, PMTUS can make a significant contribution to the conservation of the mangrove ecosystem, as with each challenge presented to the student, resolutions were sought for the social and environmental issues that affect this environment, starting to acquire the sense of citizenship through science education.